Design of a fully differential controlled gain open-loop wideband amplifier with common-mode feedback - Koo, Tiong Yin (Nanyang Technological University, 2024)
Fully differential amplifier plays an important role in eliminating the common noise and amplifying the signals. In this project, an open-loop wideband amplifier with fully differential controlled gain and common mode feedback is designed using 55nm CMOS technology. The fully differential wideband amplifier maintains the common mode output voltage at 0.9V through a common-mode feedback circuit. The 1.8V voltage supply voltage has a power dissipation of 1.80083mW (@1mA) under DC operation. With a load of 200 fF on each output, the circuit was able to produce an open-loop voltage gain of 12.02 dB and a unity gain bandwidth of 478.5 MHz. The output voltage has a -26.8dB total harmonic distortion and can swing between 0.281V and 1.415V.